ANALISIS KINERJA PEGAWAI DI INSPEKTORAT DAERAH PROVINSI SULAWESI UTARA SETELAH PENERAPAN SISTEM ELEKTRONIK KINERJA (e-KIN) - Saiyang, Januar Briand; Ilat, Ventje; Manossoh, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2022)
In an effort to implement good bolawins and results-oriented governance, the Provincial Government of North Sulawesi has made improvements to the performance of ASN which is considered to be still not meeting the standards. The North Sulawesi Provincial Government created a breakthrough to improve employee performance with a system connected to technology called Electronic Performance (e-Kin) which is useful for measuring the performance of all State Civil Apparatuses to improve the performance of government officials. In its application, there are problems that arise because the distribution of types of activities can be accessed by all ASN, although in accordance with the Main Tasks and Functions of different Regional Apparatus Organizations and the weight of performance points is not appropriate and proportional to the type of activity or activity carried out. The results of this study indicate that the implementation of e-Kinerja of Regional Inspectorate employees is not fully in accordance with the purpose of the application of e-Kinerja itself, namely to solve problems of performance and welfare of the ASN of the Regional Inspectorate of North Sulawesi Province. Therefore, efforts are needed, namely: e-Kin has clear, efficient, effective benchmarks and is monitored and supervised by direct superiors through the e-Kin system.